An Eyewitness Account: Considering Facebook Watch to Cultivate EFL Learners' Intercultural Competence - Ghaffour, Mohamed (Universitas Jambi, Magister Program of English Education Department, 2024)
Intercultural competence (IC) is a salient element that EFL students should possess to communicate effectively and appropriately in today's world. (Byram, 1997) Scholars differed on what constitutes IC, however, there is somehow a consensus that an intercultural speaker is an individual that possesses intercultural knowledge, intercultural attitudes, and intercultural behaviors. Drawing on a long experience in Facebook, this paper discusses how we can utilize Facebook watch feature as a mobile technology tool to aid EFL learners in developing intercultural competence. Following an experience-driven research design, we relied on a digital auto-ethnography research approach to generate introspective data for analysis. We explained how exposure to Chewkz (Facebook content creator) storytimes and real-life roleplay videos could help the author develop their intercultural knowledge, skills, and attitudes. We speculate that similar results can be reproduced by adopting appropriate and convenient videos vis-Ã -vis the context. Indeed, we rejected 29 videos out of 43 because they had inappropriate content, which we believe does not serve our students' best needs and thus results in unfavorable results.